2014
DOI: 10.1115/1.4026943
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Investigations of a Bypass Dual Throat Nozzle

Abstract: The bypass dual throat nozzle (BDTN) is a new kind o f fluidic vec toring nozzle. A bypass is set between the upstream convergent section and upstream minimum area based on the conventional dual throat nozzle (DTN). The BDTN shows a minimum or even no penalty on the nozzle's thrust performance, while it would be able to produce steady and efficient vectoring deflection similar to the conventional DTN. A BDTN model has been designed and sub jected to experimental and computational study. The main results show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
51
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 16 publications
6
51
1
Order By: Relevance
“…15,16 However, the results of this study demonstrated that the thrust efficiency of the nozzle was not enhanced because of the normal shock wave located in the cavity. Other computational and experimental researches were also executed [17][18][19] and a twodimensional (2D) divergent DTN was investigated to acquire large thrust vector angles. [19][20][21] For the divergent DTN, as the NPR increases, the normal shock wave begins to appear and moves downstream, but remains inside the cavity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 However, the results of this study demonstrated that the thrust efficiency of the nozzle was not enhanced because of the normal shock wave located in the cavity. Other computational and experimental researches were also executed [17][18][19] and a twodimensional (2D) divergent DTN was investigated to acquire large thrust vector angles. [19][20][21] For the divergent DTN, as the NPR increases, the normal shock wave begins to appear and moves downstream, but remains inside the cavity.…”
Section: Introductionmentioning
confidence: 99%
“…Other computational and experimental researches were also executed [17][18][19] and a twodimensional (2D) divergent DTN was investigated to acquire large thrust vector angles. [19][20][21] For the divergent DTN, as the NPR increases, the normal shock wave begins to appear and moves downstream, but remains inside the cavity. In addition, the shock wave structure is not changed with the increase of in the NPR.…”
Section: Introductionmentioning
confidence: 99%
“…Later, a new kind of FTVC nozzle called by bypass dual-throat nozzle was established and investigated. Gu et al 11 carried out the numerical and experimental studies on steady characteristics of the bypass dual-throat nozzle. It was evident that it can offer the higher thrust efficiencies in some operating conditions, compared with other FTVC methods.…”
Section: Introductionmentioning
confidence: 99%
“…While modern fluidic nozzles are designed and developed to increase the thrust vectoring efficiency (14) , to the author's knowledge, limited academic research has been performed on fluidic nozzles, especially multi-directional cylindrical ones. In general, parameters that affect the flow ability to remain attached to the curved surface include the free-stream velocity, radius of curvature, slot location and size (height and span) and blowing pressure (15) .…”
Section: Introductionmentioning
confidence: 99%